A novel fluorescent assay for oxytetracycline hydrochloride based on fluorescence quenching of water‐soluble CdTe nanocrystals. (19th June 2012) - Gao, Chao; Liu, Zhen; Chen, Jianqiu; Yan, Zhengyu
ABSTRACT: A novel assay for oxytetracycline hydrochloride (OTC) based on fluorescence quenching was developed from the interaction between functionalized cadmium telluride quantum dots (CdTe QDs) and OTC. Optimum conditions for the detection of OTC were found after investigating all factors. Under optimum conditions, luminescence of CdTe nanocrystals (λex  = 365 nm, λem  = 562 nm) was quenched by OTC in a concentration‐dependent manner best described by a modified Stern‐Volmer type equation. Good linearity was obtained with a regression coefficient of 0.9999 in the range of 1.34 ~ 13.4 x 10 ‐5  mol/L and a limit of detection of 3.08 x 10 ‐7  mol/L. In addition, the quenching mechanism was also established. The results imply that the close proximity of OTC‐CdTe was driven by electrostatic attraction and the resulting effective electron transfer from OTC to QDs could be responsible for fluorescence quenching of CdTe‐QDs. Copyright © 2012 John Wiley & Sons, Ltd.